2016
DOI: 10.1038/ncomms10238
|View full text |Cite
|
Sign up to set email alerts
|

Global proteogenomic analysis of human MHC class I-associated peptides derived from non-canonical reading frames

Abstract: In view of recent reports documenting pervasive translation outside of canonical protein-coding sequences, we wished to determine the proportion of major histocompatibility complex (MHC) class I-associated peptides (MAPs) derived from non-canonical reading frames. Here we perform proteogenomic analyses of MAPs eluted from human B cells using high-throughput mass spectrometry to probe the six-frame translation of the B-cell transcriptome. We report that ∼10% of MAPs originate from allegedly noncoding genomic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 208 publications
(218 citation statements)
references
References 71 publications
12
192
0
Order By: Relevance
“…MiHA identification is probably more efficient when EBV-LCLs are used that have been SNP genotyped more extensively, for example, by whole-genome sequencing. Recently, it has been demonstrated that a proportion of the HLA ligandome is encoded by "noncoding" genomic regions that are not known to contain functional genes (35). Here, we confirm that these genomic regions indeed encode relevant T cell epitopes, as illustrated by the characterization of LB-C16ORF-1R as a novel MiHA that is targeted by CD8 T cells in the setting of alloSCT and DLI.…”
Section: Methodssupporting
confidence: 77%
“…MiHA identification is probably more efficient when EBV-LCLs are used that have been SNP genotyped more extensively, for example, by whole-genome sequencing. Recently, it has been demonstrated that a proportion of the HLA ligandome is encoded by "noncoding" genomic regions that are not known to contain functional genes (35). Here, we confirm that these genomic regions indeed encode relevant T cell epitopes, as illustrated by the characterization of LB-C16ORF-1R as a novel MiHA that is targeted by CD8 T cells in the setting of alloSCT and DLI.…”
Section: Methodssupporting
confidence: 77%
“…To obtain a comprehensive representation of the immunopeptidome presented by HLA-A and HLA-B molecules, we applied a well-validated high-throughput proteogenomic approach that hinges on a combination of next-generation sequencing and high-throughput MS (20,27,28). Transcriptome soned that if our MS analyses randomly missed some MAPs, the proportion of MAP source versus nonsource genes should nevertheless follow a binomial distribution where the number of source genes increases as a function of the number of detected MAPs (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…According to the dominant paradigm, MAPs preferentially originate from defective ribosomal products (DRiPs) which can be created by several mechanisms such as nonsense-mediated decay (NMD), mRNA destabilization, or noncanonical translation in the cytosol or the nucleus (16)(17)(18)(19)(20). Large-scale mass spectrometry (MS) offers the sole direct approach to analyzing the global molecular composition of the immunopeptidome.…”
Section: Introductionmentioning
confidence: 99%
“…These unusual translation products are referred to as cryptic peptides and form a substantial and significant part of the overall pMHC I repertoire (19). When Perreault and colleagues examined the MHC I associated peptides with mass spectrometry, they discovered ~10% of these peptides were actually encoded by transcripts normally considered to be untranslated.…”
Section: Discovery Of Cryptic Peptides In the Pmhc I Repertoirementioning
confidence: 99%